2020
DOI: 10.1007/s13555-020-00386-8
|View full text |Cite
|
Sign up to set email alerts
|

Risankizumab-Aggravated Crusted Scabies in a Patient with Down Syndrome

Abstract: Risankizumab, an interleukin (IL)-23 antagonist, is a highly effective treatment for moderate to severe psoriasis. Crusted scabies (CS) is a rare and severe form of scabies, occurring mainly in immunosuppressed patients and/or neurologically or mentally ill patients. A young girl with Down syndrome was diagnosed with a hyperkeratotic form of psoriasis. As treatment with topical dermocorticosteroids, UVB-phototherapy and acitretin for 6 weeks did not improve the lesions, two injections of risankizumab were admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Dupilumab blocks the activity of interleukin 4 (IL-4) and IL-13, 2 key cytokines of the helper T cell 2 immune response that are essential in fighting parasites 1 . Although no data on a possible increase of Norwegian scabies with dupilumab therapy have been reported up to date, cases have been published in the context of other biological therapies that inhibit important cytokines of the helper T cell 2 route (anti–IL-23, anti–tumor necrosis factor) 2–5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dupilumab blocks the activity of interleukin 4 (IL-4) and IL-13, 2 key cytokines of the helper T cell 2 immune response that are essential in fighting parasites 1 . Although no data on a possible increase of Norwegian scabies with dupilumab therapy have been reported up to date, cases have been published in the context of other biological therapies that inhibit important cytokines of the helper T cell 2 route (anti–IL-23, anti–tumor necrosis factor) 2–5 …”
Section: Discussionmentioning
confidence: 99%
“…1 Although no data on a possible increase of Norwegian scabies with dupilumab therapy have been reported up to date, cases have been published in the context of other biological therapies that inhibit important cytokines of the helper T cell 2 route (anti-IL-23, anti-tumor necrosis factor). [2][3][4][5] PEARL Norwegian scabies should be considered in any outbreak of new-onset pruritic dermatitis in dupilumab-treated patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was 1 observational study of a scabies outbreak among persons with mental disability, which reported an index case of a 16-year-old patient with DS [79]. There were also 7 case reports of scabies (Multimedia Appendix 6) [15,16,[80][81][82][83][84], where 4 of the cases reported an initial misdiagnosis of scabies, and the patients were instead treated ineffectively for presumed onychomycosis, psoriasis, eczema, tinea corporis, and psoriasiform dermatitis [16,[80][81][82]84]. There were also 4 case reports of leishmaniasis (Multimedia Appendix 7) [74,[85][86][87] and 1 case report of actinomycetoma [88].…”
Section: Other Infectionsmentioning
confidence: 99%
“…28,63 Also, several informative case reports describing crusted scabies initially misdiagnosed as psoriasis and inappropriately treated with immunosuppression are found. [64][65][66][67] Crusted scabies may be more common in DS given underlying immunodeficiency and immune dysregulation; it is well documented that immunocompromised patients are at increased risk of developing crusted scabies. Given this knowledge, crusted scabies should be on the differential diagnosis when a patient with DS presents with generalized erythrodermic dermatitis, keratoderma, or onychodystrophy.…”
Section: Infections and Infestationsmentioning
confidence: 99%